2-(3,5-Di-tert-butyl-4-hydroxybenzylsulfanyl)-N'-(3-methoxybenzylidene)-acetohydrazide - Ariffin, Azhar; Ng, S.W.; Yehye, W.A.; Rahman, N.A. (International Union of Crystallography, 2009)
The title compound, C25H34N2O3S, is a derivative of N '-benzylideneacetohydrazide having substituents on the acetyl and benzylidenyl parts, and displays a planar C-carbonyl-NH-NCanisyl fragment [torsion angle = 174.9 (3)degrees]. The -NH- unit forms an N-H center dot center dot center dot O hydrogen bond with the carbonyl O atom of an inversion-related molecule.